Budget Control and Organizational Performance of Local Government in Darchula District (Far Western Review, 2025)
The study aims to examine how budget control affects the performance of local government in Darchula district, taking into account the role of employee motivation. The study used a quantitative approach that combined descriptive and causal-comparative research designs with primary data. Out of 246 employees, 150 were sampled. A total of 200 questionnaires were distributed, and 165 completed questionnaires were returned. The results shown that budgetary guidelines and participation have the strongest positive effect on organizational performance, followed by monitoring and performance measure. However, training and effectiveness of budget show a weaker impact, suggesting the need for improved training and effectiveness strategies of budget. Additionally, the study confirms that employee motivation significantly mediates the relationship between budget control and organizational performance. Budget control of local government in Darchula district has a significant and positive impact onorganizational performance, the combined effect of budget control and motivation has found stronger rather than single effect. Budget control has a significant and positive impact on organizational performance, and the combined effect of budget control and employee motivation has a strong synergy in driving better outcomes. The findings of the study will be useful to the officers of local government for the implementation of budget control dimensions (structured budget guidelines, participation, training, and monitoring systems) to enhance public sector accountability and efficiency. The future research will need to address the qualitative issues and explore the ways of budget control within the various government sectors.